A New Characterization of k-Uniformly Rotund Banach Space - Suyalatu Wulede; Tingting Li; Xuan Qin (Journal of Function Spaces)
A new characterization of k-uniformly rotund Banach space with 1<P<+∞ is given. Moreover, a corresponding result in the locally k-uniformly rotund Banach space with 1<P<+∞ is given.